Karakteristik Jaringan Jalan dan Keterbukaan Tanah Hutan Akibat Kegiatan Pembukaan Wilayah Hutan (Studi Kasus di IUPHHK-HA PT Sindo Lumber Kalimantan Tengah): Characteristics of The Roads Network and Openness Forest Land Due to Activity Forest Opening Area-Case Study at IUPHHK-HA PT Sindo Lumber Central Kalimantan - Ajun Junaedi; I Nyoman Surasana; Mohammad Rizal; Santa Tri Dwi Sartika Waruwu (HUTAN TROPIKA, 2021)
The purpose of this study: a) to determine the characteristic parameters the forest roads network, such as: density forest roads, spacing forest roads, average distance skid trails, correction factor and quality forest opening area; (b) calculate the percent openness forest land due to activities making main roads network, branch roads, skid trail and TPn. The location research in block harvesting RKT 2018 at IUPHHK-HA PT Sindo Lumber Central Kalimantan. The results showed density the forest roads network ranged between 7.96 – 17.66 m/ha, 1256.28 m main road spacing, 1097.69 m branch road spacing, 566.25 m skid trail spacing, 146.5 m average distance skid theoritical (REo), 186.83 m REm and 252.30 m REt. The correction factor value of the roads network (Vcorr), Tcorr and the correction factor forest opening area (KG) respectively by 1.27, 1.35 and 1.71 with the quality forest opening area included in the category of “very good”. While the percent of the openness forest land due to making main roads network, branch roads, skid trail and TPn respectively by 0.87%, 0.73%, 3% and 0.53%.